2020
DOI: 10.1088/1742-6596/1665/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

The cyanidin-3-O-glucoside of Black Rice inhibits the interaction of HMG-CoA and HMG-CoA Reductase: three-and two-dimension structure

Abstract: The hypercholesterolemia condition is one metabolic disorder has affected to onset and prevalence of the dyslipidemia and cardiovascular disease. The cholesterol synthesized from HMG-CoA by co-enzyme HMG-CoA reductase. The research focus was to determine the effect of Cyanidin-O-glucose of black rice to prevent the HMG-CoA and HMG-CoA reductase interaction. The anthocyanins retrieved from the database of PubChem, is cyanidin-3-O-glucoside (CID: 12303221). We obtained HMG-CoA canonical SMILES (CID: 445127) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…From studied anthocyanins, only cyanidin‐3‐O‐rutinoside and pelargonidin‐3‐O‐rutinoside showed moderate activity on HMG‐CoA reductase (Table 2). To the best of our knowledge, there is not any other biochemical evidence suggesting the interaction of this anthocyanin with HMG‐CoA reductase, however, recent in silico approaches advise that cyanidin‐3‐O‐glucoside from black rice inhibits the interaction of HMG‐CoA with HMG‐CoA reductase [19] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From studied anthocyanins, only cyanidin‐3‐O‐rutinoside and pelargonidin‐3‐O‐rutinoside showed moderate activity on HMG‐CoA reductase (Table 2). To the best of our knowledge, there is not any other biochemical evidence suggesting the interaction of this anthocyanin with HMG‐CoA reductase, however, recent in silico approaches advise that cyanidin‐3‐O‐glucoside from black rice inhibits the interaction of HMG‐CoA with HMG‐CoA reductase [19] …”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there is not any other biochemical evidence suggesting the interaction of this anthocyanin with HMG-CoA reductase, however, recent in silico approaches advise that cyanidin-3-O-glucoside from black rice inhibits the interaction of HMG-CoA with HMG-CoA reductase. [19] RPAF had an evident anti-ODC activity (IC 50 , 150 μg mL À 1 ) (Table 2). Interestingly, all assayed anthocyanins showed differential inhibitory capacity on this enzyme (p < 0.05).…”
Section: Inhibitory Properties Of Rpaf and Pure Anthocyanins On Targe...mentioning
confidence: 98%
“…Cyanidin-3-O-glucoside and peonidin-3-O-glucoside are predicted to have anti-apoptosis effect by inhibiting caspase-3 (Sari et al, 2020a). In vivo and in-silico studies have proven that black rice anthocyanins act against obesity and adipogenesis (Fatchiyah et al, 2020b, Fatchiyah et al,2020cSari et al, 2020b). In the current study, , anthocyanins were not detected in RREJ red rice fraction containing pigment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies identified malvidin (Chen et al, 2012) and proanthocyanidin, rather than anthocyanins, as the pigments found in high amounts Figure 4. Summary of genomic, proteomic, and anthocyanin profiles in black rice from Java island, numerical superscripts indicate the data derived from previous studies: 1 (Fatchiyah et al, 2020a), 2 (Fatchiyah et al, 2020b), 3 (Sari et al, 2020b), 4 (Sari et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Ki (Konstanta Penghambatan ) nilai kompleks statin-enzim berkisar antara 0,1 hingga 2,3 nM, sedangkan konstanta Michaelis, untuk HMG-CoA adalah 4 M. Proteinnya membentuk tetramer yang terkait erat dengan situs aktif bi-partit, yang bertetangga monomer menyumbangkan residu menjadi aktif situs. Kantong pengikat HMG ditandai dengan lingkaran (residu 682-694, disebut sebagai "cis loop") [8]. Karena statin bersifat kompetitif sehubungan dengan HMG-CoA, itu sepertinya bagiannya mirip pengikatan HMG pada situs aktif enzim.…”
Section: Hasil Dan Pembahasanunclassified